2022
DOI: 10.4103/aam.aam_79_20
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis: Is the prevalence increasing in Saudi Arabia

Abstract: Background and Objective: The objective of this analysis is to report from a teaching hospital in eastern Saudi Arabia hospital based prevalence of osteopenia and osteoporosis. Methods: This is a retrospective study of all patients who underwent dual-energy X-ray absorptiometry (DXA) scan between January 1, and December 31, 2018, at King Fahd Hospital of the University at Alkhobar, Saudi Arabia. Demographic data of patients, which included age, sex, diabetes mellitus st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The purpose of our study is to gain more insight into and understanding of the prevalence of osteoporosis and osteopenia among the geriatric population; the prevalence of osteoporosis was 8.2% and 11.8% based on femoral and lumbar results, respectively. When comparing our data to previously published articles in Saudi Arabia, a recently published article by Sadat-Ali et al showed the prevalence to be 52.8% in women and 63.6% in men using the T-score of the lumbar spine [8]. AlQuaiz et al reported that screening of 362 healthy women using DEXA revealed that 58.6% had low bone density; however, this group comprised only women between 40 and 50 years old [21].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The purpose of our study is to gain more insight into and understanding of the prevalence of osteoporosis and osteopenia among the geriatric population; the prevalence of osteoporosis was 8.2% and 11.8% based on femoral and lumbar results, respectively. When comparing our data to previously published articles in Saudi Arabia, a recently published article by Sadat-Ali et al showed the prevalence to be 52.8% in women and 63.6% in men using the T-score of the lumbar spine [8]. AlQuaiz et al reported that screening of 362 healthy women using DEXA revealed that 58.6% had low bone density; however, this group comprised only women between 40 and 50 years old [21].…”
Section: Discussionsupporting
confidence: 67%
“…In Saudi Arabia, a few studies have estimated the prevalence of osteoporosis among adults ranging from 23.4% to 39.5%; however, most of these studies date back more than 15 years [4][5][6][7]. The most recent estimate of osteoporosis in Saudi Arabia is 52.8% of women and 63.6% of men in a hospital-based setting [8]. Around 200 million people over the world have osteoporosis, causing more than 8.9 million fractures yearly [9].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis affects 30% of all postmenopausal women in the USA and Europe [ 10 , 11 ]. In Saudi Arabia, recent studies found that OP affects 53% of Saudi women [ 12 ]. OP appears to occur at a younger age in the Saudi population when compared to the western counterparts [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of osteoporosis in Saudi Arabia is increasing [4]. Since osteoporotic fractures have become more prevalent with advancing age, preventing osteoporosis and its complications is a critical public health concern [1].…”
Section: Introductionmentioning
confidence: 99%